Financial Distress: Ratio of Financial Statements of Mining And Metals Companies - Pebriani, Reny Aziatul; Syafitri, Lili; Meiriasari, Vhika (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
This research aims to determine the influence of profitability, leverage and liquidity on financial distress in the mining and metals company sub-sector in Indonesia during the 2018-2022 Period. Profitability is measured using Return on Assets (ROA), leverage is measured by Debt to Equity Ratio (DER), and liquidity is measured using Current Ratio (CR). Financial distress was identified using the Altman Z-score model. This type of research is a quantitative research sampling in this study using purposive sampling techniques and data that has been processed for this study as many as 11 Mining and Metal companies listed on the Indonesia Stock Exchange. The data source in this study uses a secondary data source sourced from the Annual Report published by mining and metals companies listed on the Indonesia Stock Exchange. The data analysis used in this study used Descriptive Satistic analysis, Pooled Data, Chow Test, Hausman Test, Fixed Effect, Partial Test, Determination Coefficient Test (R2). The test results showed that the Return on Asset (ROA) variable, Debt to Equity ratio (DER), did not have a significant effect on financial distress, while the Current Ratio (CR) had a significant effect on financial distress in Mining and Metal Companies listed on the Indonesia Stock Exchange in 2018-2022. The Result of this study is that profitability, leverage, and liquidity significantly affect the condition of financial distress in mining and metals sub-sector companies in Indonesia.